2011
DOI: 10.4322/natcon.2011.028
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Threatened and Endemic Atlantic Forest Birds Under Climate Change

Abstract: Knowledge of the possible impacts of climate change on biodiversity in the tropics is especially scarce. We used maximum entropy modeling of species distributions to predict the ranges of endemic and threatened Atlantic Forest birds under a "business as usual" emissions scenario for 2050. Of the 51 species with reliable models, 44 were predicted to lose distribution area, with future ranges averaging 45% of their original size. Range contraction would bring two species to IUCN's threshold for threat under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 17 publications
7
19
0
Order By: Relevance
“…Some studies have found these tendencies to geographic reduction in tropical mountain species of South America, such as the threatened birds of the northern Andes in Colombia (Velásquez-Tibatá et al, 2012) and birds of the Atlantic forest in Brazil (Vieira de Souza et al, 2011). Moreover, the geographic range reduction (63%) is not far from the projections for range-restricted birds of the northern Andes in Colombia for 2050 (33-43%) (Velásquez-Tibatá et al, 2012).…”
Section: Changes In Geographic Distribution and Conservationmentioning
confidence: 96%
“…Some studies have found these tendencies to geographic reduction in tropical mountain species of South America, such as the threatened birds of the northern Andes in Colombia (Velásquez-Tibatá et al, 2012) and birds of the Atlantic forest in Brazil (Vieira de Souza et al, 2011). Moreover, the geographic range reduction (63%) is not far from the projections for range-restricted birds of the northern Andes in Colombia for 2050 (33-43%) (Velásquez-Tibatá et al, 2012).…”
Section: Changes In Geographic Distribution and Conservationmentioning
confidence: 96%
“…All variables had a spatial resolution of 30'' (~1 km). We selected these environmental variables because they are biologically relevant to species distribution and show low collinearity (Souza et al 2011).…”
Section: Species Distribution Modelingmentioning
confidence: 99%
“…Our data are in agreement with those of previous studies showing a negative effect of climate change, reducing suitable areas for many Atlantic forest organisms, such as birds (Souza et al . ), amphibians (Haddad et al . ; Lemes et al .…”
Section: Discussionmentioning
confidence: 99%